Endolysosomal cholesterol export: More than just NPC1. (7th August 2022) - Lu, Albert
Abstract: NPC1 plays a central role in cholesterol egress from endolysosomes, a critical step for maintaining intracellular cholesterol homeostasis. Despite recent advances in the field, the full repertoire of molecules and pathways involved in this process remains unknown. Emerging evidence suggests the existence of NPC1‐independent, alternative routes. These may involve vesicular and non‐vesicular mechanisms, as well as release of extracellular vesicles. Understanding the underlying molecular mechanisms that bypass NPC1 function could have important implications for the development of therapies for lysosomal storage disorders. Here we discuss how cholesterol may be exported from lysosomes in which NPC1 function is impaired. Abstract : NPC1 plays a key role in LDL‐derived cholesterol export from endolysosomes. Recent evidence supports the existence of alternative cholesterol egress routes that act in parallel or independently of NPC1. These so‐called NPC1 bypass pathways rely on both vesicular trafficking (involving RAB proteins) and non‐vesicular transport mechanisms (i.e., membrane contacts), including viral infections.